When do parties put Europe in the centre? Evidence from the 2019 European Parliament election campaign. (November 2021) - Maier, Michaela; Jalali, Carlos; Maier, Jürgen; Nai, Alessandro; Stier, Sebastian
European elections have been described as second-order phenomena for voters, the media, but also parties. Yet, since 2009, there exists evidence that not only voters, but also political parties assign increasing significance to European elections. While initially 'issue entrepreneurs' were held responsible for this development, the latest campaigns have raised the question of whether mainstream parties are finally also campaigning on European issues. In this article, we examine European Union (EU) salience in the 2019 European Parliament (EP) campaigns of government and opposition parties and the predictors of their strategic behaviours. We test the relevance of factors derived from the selective emphasis and the co-orientation approach within an integrated model of strategic campaign communication based on expert evaluations of 191 parties in 28 EU member states. Results show that the traditional expectation that government parties silence EU issues does not hold anymore; instead, the average EU salience of government and opposition parties is similar on the national level. The strongest predictors for a party's decision to campaign on EU issues are the co-orientation towards the campaign agendas of competing parties, and party's EU position.